2007
DOI: 10.1158/0008-5472.can-07-1743
|View full text |Cite
|
Sign up to set email alerts
|

The Alternative Reading Frame Tumor Suppressor Antagonizes Hypoxia-Induced Cancer Cell Migration via Interaction with the COOH-Terminal Binding Protein Corepressor

Abstract: The alternative reading frame (ARF) tumor suppressor exerts both p53-dependent and p53-independent activities critical to the prevention of cancer in mice and humans. Recent evidence from mouse models suggests that when p53 is absent, further loss of ARF can widen the tumor spectrum, and potentiate invasion and metastasis. A major target of the p53-independent activity of ARF is the COOH-terminal binding protein (CtBP) family of metabolically regulated transcriptional corepressors, which are degraded upon acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 31 publications
5
69
0
Order By: Relevance
“…CTBP is part of the corepressor complex, CoREST and is involved in repression of tumor suppressor genes such as CDH1 (encoding E-cadherin), PTEN, and CDKN2A (37)(38)(39)(40)(41). In the present study, we found that suppression of Ctbp2, but not of Ctbp1, confers RA resistance, suggesting the unique attribute of Ctbp2 as a coactivator in RA signaling (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…CTBP is part of the corepressor complex, CoREST and is involved in repression of tumor suppressor genes such as CDH1 (encoding E-cadherin), PTEN, and CDKN2A (37)(38)(39)(40)(41). In the present study, we found that suppression of Ctbp2, but not of Ctbp1, confers RA resistance, suggesting the unique attribute of Ctbp2 as a coactivator in RA signaling (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…CtBPs have PLDS domains that interact with histone-modifying enzymes, such as HDAC, LSD1, and G9a, to modulate histone acetylation and methylation levels. Although the CTBP family is associated with cancer, the roles of CtBPs in cancer vary depending on the cancer type (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Arf inhibits the hypoxia-induced migration of H1299 human lung carcinoma cells in a p53-independent and CtBPdependent manner (35), and previous studies have indicated that CtBP can regulate the migration of this cell line, although cell invasion was not assayed in these studies (20). Significantly, the leucine 46 residue, which is critical for the Arf-CtBP interaction, is one of six invariant residues conserved across several species, including human, mouse, chicken, pig, and opossum (32).…”
Section: Discussionmentioning
confidence: 99%